PENERAPAN METODE DISKUSI UNTUK MENINGKATKAN HASIL BELAJAR PKN PADA MATERI MENDESKRIPSIKAN PENGERTIAN ORGANISASI SISWA KELAS V SD NEGERI 009 TEMBILAHAN HULU KECAMATAN TEMBILAHAN HULU - Tuti Eliani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The background of the research is lack of the ability to explain the definitions of organization. This study aims to determine whether or not there was improvement of Civics learning outcomes before and after the research was carried out by using the discussion method on Grade V students of SD Negeri 009 Tembilahan Hulu, Kecamatan Tembilahan Hulu. The number of the subject of the research was 20, consisting of 10 male students and 10 female students with heterogeneous capabilities. The research was conducted on from January 12, 2016 to February 2, 2016. The study was conducted in two cycles. Data of the research were collected from observation and tests. Observation sheet will be analyzed descriptively to describe the activities done by both teachers and students during the learning process took place, while the achievement test was analyzed by the minimum passing grade criteria, hereinafter KKM and analysis of the average was used to determine whether or not there was improvement of the students’ learning outcomes before and after application of the discussion method. Based on the data obtained from the teacher of the school, the number of the students reaching the KKM was 5 (25%) and the average score was 71.1. The research findings reveal that the number of students who reached KKM at the first cycle was 14 (70%) and at the second cycle, the number increased to 19 people (95%). The average score at the first cycle increased from the previous one to 76.3. The improvement also took place at the second cycle in which the average score was 84.7. Based on these findings, it can be concluded that the application of the discussion method can improve civics learning outcomes of Grade V students of SD Negeri 009 Tembilahan.